2021
DOI: 10.3390/genes12111783
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability of MEGF10 Variants Causing Congenital Myopathy: Report of Two Unrelated Patients from a Highly Consanguineous Population

Abstract: Congenital myopathies are rare neuromuscular hereditary disorders that manifest at birth or during infancy and usually appear with muscle weakness and hypotonia. One of such disorders, early-onset myopathy, areflexia, respiratory distress, and dysphagia (EMARDD, OMIM: 614399, MIM: 612453), is a rare autosomal recessive disorder caused by biallelic mutations (at homozygous or compound heterozygous status) in MEGF10 (multiple epidermal growth factor-like domains protein family). Here, we report two unrelated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…After library preparation, captured fragments were run on an Illumina HiSeq 2500 Sequencer and mapped against UCSC hg19 (Illumina, Inc., San Diego, CA, United States). Comprehensive filtering of the detected variants was done as previously published (8)(9)(10)(11). Especially, variants based on homozygosity, coding, and splicing features, being within the autozygome of the affected individuals in the families, were prioritized during filtering analysis.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…After library preparation, captured fragments were run on an Illumina HiSeq 2500 Sequencer and mapped against UCSC hg19 (Illumina, Inc., San Diego, CA, United States). Comprehensive filtering of the detected variants was done as previously published (8)(9)(10)(11). Especially, variants based on homozygosity, coding, and splicing features, being within the autozygome of the affected individuals in the families, were prioritized during filtering analysis.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…Additionally, publicly available databases and local resources, such as the program for Saudi Human Genome-based data outputs, were also screened during filtering. In silico pathogenicity was carried out as reported before (8)(9)(10)(11).…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…The MEGF10 gene encodes the multiple EGF-like domain 10 protein, a transmembrane receptor belonging to the multiple epidermal growth factor–like domains family, that is upregulated in activated satellite cells and regulates the progression of the myogenic program ( Holterman et al, 2007 ). Mutations in MEGF10 have been detected in a few cases of MmD ( Boyden et al, 2012 ; Liewluck et al, 2016 ; Takayama et al, 2016 ; AlMuhaizea et al, 2021 ). The CACNA1S gene encodes Cav1.1, the pore-forming subunit of the skeletal muscle voltage-gated Ca 2+ channel (DHPR).…”
Section: Ryr1 -Related Myopathiesmentioning
confidence: 99%
“…Various MEGF10 mutations have so far been identified in patients with neuromuscular disorders, such as minicore myopathy, LGMD, and early onset myopathy, areflexia, respiratory distress, and dysphagia (EMARDD). This report by AlMuhaizea and co-workers [ 3 ] contributes to the list of known pathogenic MEGF10 mutations and their genotype–phenotype correlations. A case report is also included in this Special Issue, authored by Serrano-Lorenzo and coworkers [ 4 ], which focuses on metabolic myopathies.…”
mentioning
confidence: 91%
“…In a brief report, AlMuhaizea and co-workers [ 3 ] describe two novel variants of MEGF10 identified in two unrelated patients with congenital myopathies who were born to consanguineous parents from Saudi Arabia. Furthermore, the authors reviewed the literature and provided a list of the previously reported pathogenic variants of MEGF10 and the associated congenital myopathies.…”
mentioning
confidence: 99%